Aktiv, Passiv und anderes mehr: учебно-методическое пособие / Г. С. Рязанцева, Е. С. Ошанова - Рязанцева Галина Сергеевна (УИР ИжГТУ имени М. Т. Калашникова, 2020)
Экземпляры: УКП (20211124) / Инвентарный номер: АП20200523 / Сис.шифр: 81.432.4-923 / Авт.знак: Р 99 / ГРНТИ: 16.41.21 / ББК: 81.432.4-923